Candida albicans isolated from post-operative penetrating keratoplasty patient: Case report - Chandra, Abhishek; Gupta, Munesh Kumar; Tilak, Ragini (Asian Journal of Medical Sciences, 2014)
We report a case report of Candida albicans suture infiltrate on 3rd post-op day in a 53 year female operated for penetrating keratoplasty. Candida albicans was identified by KOH mount, Gram Staining, germ tube, growth at 450C, chlamydospore formation and light green color on CHROMagar with sugar assimilation and culture characteristics. Despite being susceptible to Fluconazole by broth microdilution, patient did not respond to 0.3% fluconazole eye drops. On antifungal susceptibility testing by CLSI44A, it was susceptible to only Amphotericin B (100units). Patient was then started on 0.15% fortified amphotericin B eye drops resulting in complete resolution of infiltrates. Asian Journal of Medical Science, Volume-5(3) 2014: 116-119 http://dx.doi.org/10.3126/ajms.v5i3.8669